(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
Even though, nowadays, advertising is an area frequently studied from the point of view of the Critical Discourse Analysis (CDA), there is no information regarding the use of English in advertising broadcast in Chilean magazines. In this context, the aim of this study was to determine the percentage of advertising broadcast in the English language within Chilean magazines of national circulation. In order to achieve this, 632 advertisements that appeared in “Mujer”, “M” and “Ya” magazines were analysed. Results showed that 7% of advertising occurs exclusively in English, 41% of the messages are written only in Spanish, and 52% of the advertising messages use both languages. The products whose advertising is only in English are not intended to meet basic necessities. Finally, there are marked patterns between the types of products and the use they make of these two languages.